How is Information and Communication Technology used in the Indonesian Government? A Sciencetometric Analysis - Lawelai, Herman; Misran; Baulete, Elaine; Tenorio, Christine B.; Prakoso, Velandani (Konsultan Surya Buanan, 2024)
This study aims to analyze publication trends related to the ICT Government in Indonesia with a scientomertic approach. This study uses data analysis methods from Scopus with RStudio, VOSviewer, and CiteSpace applications to visualize and analyze publications. The findings show that Indonesian authors dominate ICT Government research with 172 documents, while the contributions of authors from Malaysia, the United States, and the Netherlands provide an important international perspective. The main research topics include e-government, smart cities, and sustainable development. The findings demonstrate the role of ICTs in improving government efficiency, transparency, and civic engagement. However, publications declined in 2022, possibly due to changing research priorities or the impact of the COVID-19 pandemic. The implication of this study is the importance of international collaboration and improved technological infrastructure. The limitation of this study is the limited data that is only taken from Scopus, and it does not include analysis of interviews or direct observations that can enrich the understanding of ICT government implementation.